Low Frequency of Viral Respiratory Tract Infections During Family-Centered Neonatal Intensive Care: Results of a Prospective Surveillance Study - Kidszun, André; Neurohr, Anna; Gröndahl, Britta; Tippmann, Susanne; Schreiner, Daniel; Winter, Julia; Mahmoudpour, Seyed Hamidreza; Gehring, Stephan; Mildenberger, Eva (Frontiers in Pediatrics, 2020)
Background: Viral respiratory tract infections (VRTI) may cause severe respiratory and sepsis-like symptoms in infants hospitalized in the neonatal intensive care unit (NICU). Little is known about the frequencies of VRTI in relation to visiting policies in the NICU. Objective: Aim of this study was to evaluate the frequency of symptomatic and asymptomatic VRTI in our family-centered NICU. Methods: This was a 12-month, prospective, observational study from February 2018 to January 2019. Infants hospitalized ≥72 hours were eligible for the study. To determine the frequency of VRTI, multiplexed point-of-care testing (mPOCT) of symptomatic infants was combined with a weekly screening of all infants. Our 10-bed NICU is 24/7 open to families and visitors. The number of simultaneous visitors is restricted to two per patient. Parents and visitors are instructed in hand hygiene and advised to avoid visits in cases of respiratory illness. Siblings irrespective of age may visit the NICU following a physical check-up. Results Multiplexed point-of-care testing (75 symptomatic episodes) combined with the weekly screening (272 episodes) yielded in 17 positive samples from 2 of the 67 infants enrolled in the study. Both infants were first detected during symptomatic episodes. Rhino-/enterovirus were detected in all cases. Conclusion: Respiratory viruses were detected during symptomatic and asymptomatic episodes but affected <3 % of infants enrolled in the study. A low frequency of VRTI may be attained despite adherence to family integrated care including liberal visiting policies for younger siblings.